(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
With an emphasis on improving corporate effectiveness and employee well-being, this study explores how social awareness and information technology (IT) are changing human resource (HR) practices. The study focuses on two primary goals: (1) identifying programs and resources that support employee mental health, such as mental health days and Employee Assistance Programs (EAPs); and (2) investigating tactics that encourage candid and open communication in addition to frequent feedback and employee training. This study highlights the relationship between organizational culture, mental health awareness, and technology developments in influencing HR practices by using a conceptual framework. It looks at how efforts like wellness initiatives, flexible work schedules, and ongoing feedback systems help create a positive work atmosphere that supports mental well-being, lowers stress levels, and boosts job satisfaction. The study also looks at how leaders can foster a culture of open communication by utilizing resources like staff training and feedback mechanisms to increase engagement and trust. The results emphasize how crucial it is to integrate technology and social consciousness in order to create HR procedures that put the success of the company and the welfare of individuals first. For HR professionals looking to create tactics that foster a productive, healthy, and communicative workplace, this article provides insightful information.